Dynamic factors in the current process of language internationalisation (on the material of Czech and Polish) - Lotko, Edvard (Bohemica Olomucensia, 2012)
Some dynamic factors have been working before, but another are influencing and stimulating the inovational processes as late as now (after 1989). The contribution deals with the complicated character of dynamics of the lexical system too. The analysis of inovational processes in the lexical system confirms the basic thesis that the variability of language on one side and "flexible stability" on another side make the language not only the most perfect, but also the most complicated instrument of social interaction.